The Impact of Thymidylate Synthase and Methylenetetrahydrofolate Reductase Genotypes on Sensitivity to 5-Fluorouracil Treatment in Colorectal Cancer Cells - Fakhraddin Naghibalhossaini; Marzieh Shefaghat; Amirata Mansouri; Hajar Jaberi; Mohsen Tatar; Ebrahim Eftekhar (Acta Medica Iranica, 2018)
5-fluorouracil (5-FU) is one of the major components of many standard regimens for chemotherapy of colorectal cancer (CRC) and some other malignancies. Given the known relationship between thymidylate synthase (TS) and methylenetetrahydrofolate reductase (MTHFR) activity and 5-FU metabolism, this study investigated the impact of selected functional polymorphisms of the TS and MTHFR genes on chemotherapy resistance in 5 human CRC cell lines. HCT116, SW1116, HT29/219, LS180, and Caco-2 CRC cells were cultured as monolayer and their chemosensitivity to 5-FU, oxaliplatin, and irinotecan was determined by MTT assay. Genomic DNA was extracted from the cultured cells, and a 6-bp insertion or deletion (6-bp ins/del) polymorphism in 3´-UTR of the TS gene was determined by the PCR-RFLP method. Genotyping of MTHFR 677 C/T and 1298A/C single nucleotide polymorphism (SNP) was also performed by MS-PCR and PCR-RFLP, respectively. Caco-2 with the homozygous TS 6-bp ins/ins and MTHFR 677 T/T and 1298 C/C genotype, was the most 5-FU resistant cell line. HCT116 with the homozygous TS 6-bp del/del and MTHFR 1298 A/A and heterozygous MTHFR 677 C/T genotype was the least 5-FU resistant cell. LS180, the second most 5-FU resistant cell line, was heterozygous for all three polymorphic sits. HT29/219 and SW1116 cells with homozygous TS 6-bp ins/ins and heterozygous MTHFR 677 C/T and 1298 A/C genotypes had intermediate 5-FU sensitivity. The results indicate that TS 3´-UTR 6-bp insertion and MTHFR 677T and 1298C alleles increase 5-FU resistance in CRC cells. No relationship was observed between TS and MTHFR genotypes and oxaliplatin or irinotecan sensitivity in these cells.